2019
DOI: 10.1590/1678-7757-2018-0075
|View full text |Cite
|
Sign up to set email alerts
|

Effect of radiant exposure and UV accelerated aging on physico-chemical and mechanical properties of composite resins

Abstract: Currently, there is no consensus in terms of defining the minimum radiant exposure values necessary for achieving adequate properties of composite resin. In addition, the long-term influence that radiant exposure has on the properties of composite resins is still questionable. Objective: The objective of this study was to evaluate the effect of radiant exposure and UV accelerated aging on the physico-chemical and mechanical properties of micro-hybrid and nanofilled composite resins. Material and Methods: A nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 34 publications
1
1
0
1
Order By: Relevance
“…Future work should, therefore, investigate the monomer elution using HPLC. The results of the current study also suggest that the DC of composites mixed with the color modifier was increased by ~10% after extending the light-curing time from 20 to 40 s. This could be due to the increase in the radiant exposure, which could promote the production of free radicals [39] to enhance the DC of the materials [40,41]. Another method to enhance the polymerization could be the use of a high-irradiance light-curing unit [42].…”
Section: Discussionsupporting
confidence: 50%
“…Future work should, therefore, investigate the monomer elution using HPLC. The results of the current study also suggest that the DC of composites mixed with the color modifier was increased by ~10% after extending the light-curing time from 20 to 40 s. This could be due to the increase in the radiant exposure, which could promote the production of free radicals [39] to enhance the DC of the materials [40,41]. Another method to enhance the polymerization could be the use of a high-irradiance light-curing unit [42].…”
Section: Discussionsupporting
confidence: 50%
“…Previous studies suggested that the liberation of monomers induces damage to the DCR surface by physical and chemical causes (24,25) . The micromorphology of the DCR surface after being immersed in artificial saliva, ethanol or acid solution revealed damage with degradation of the organic matrix evidenced by erosion like pores and cracks to a big lagoon with filler particles protruding from the surface (25)(26)(27)(28) .…”
Section: Introductionmentioning
confidence: 99%
“…Estudos in vitro demandam menos tempo e custo para serem realizados, quando comparados a estudos clínicos 107 , porém há limitações inerentes. O sistema de Envelhecimento Artificial Acelerado tem sido utilizado para testes em resinas compostas desde 1978 [108][109][110][111] e reproduz os efeitos atmosféricos que ocorrem quando os materiais são expostos à luz solar e umidade. Este método tem sido utilizado para prever as mudanças físicas de vários tipos de materiais dentários, em condições bucais.…”
Section: Considerando Que ∆Eunclassified